Memahami Firman Tuhan dalam Pendekatan Logika: Refleksi Praktis Menggali Makna Firman Tuhan - Jiffry Kawung; Natalia Lahamendu; Fienny M. Langi (Institut Agama Kristen Negeri Manado, 2022)
This article describes that understanding God's Word is very important by using a Logical approach as the ability to think or reason to study and analyze God's Word so as not to get caught up in mistakes or misguided thinking. The author uses a descriptive qualitative methodology with data collection techniques for library research/library research and is supported by facts among Christians based on information from several Christian religious figures. This article is expected to provide benefits for the development of knowledge in the field of Theology and Christian Religious Education for both lecturers and students so that there needs to be a Logic Course in the Structure of the Theology and Christian Religious Education curriculum in every Christian religious college.